EMPLOYEES STRESS RESISTANCE IN ENSURING THE EFFICIENCY OF BUSINESS COMMUNICATIONS - Раупов, Рустам (Modern engineering and innovative technologies, 2022)
The article examines the concepts of stress and stress resistance in the context of ensuring the effectiveness of business communications at enterprises. The main characteristics of professional stress, stress factors that cover politics, the structure o